2021
DOI: 10.3389/ffgc.2021.655769
|View full text |Cite
|
Sign up to set email alerts
|

Sphaeropsis sapinea and Associated Endophytes in Scots Pine: Interactions and Effect on the Host Under Variable Water Content

Abstract: The ascomycete Sphaeropsis sapinea is the causal agent of the Diplodia Tip Blight disease on pines and other conifer species. This fungus has a symptomless endophytic life stage. Disease symptoms become visible when trees have been weakened by abiotic stress, usually related to warmer temperatures and drought. Currently, this disease is observed regularly in Scots pine (Pinus sylvestris) sites in parts of Europe, such as Germany, increasing dramatically in the last decade. Changes in climatic conditions will g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 94 publications
6
41
0
Order By: Relevance
“…Cleary et al [27] suggested that this endophyte is an opportunistic pathogen, in that due to changes in climate, it could increase its pathogenicity. However, Blumenstein et al [13] showed that drought stress in the host did not increase pathogenicity of Sy. polyspora, indicating that it is a true endophyte of Scots pine.…”
Section: Culture-based Isolation and Hts Methods Complement Each Othermentioning
confidence: 98%
See 4 more Smart Citations
“…Cleary et al [27] suggested that this endophyte is an opportunistic pathogen, in that due to changes in climate, it could increase its pathogenicity. However, Blumenstein et al [13] showed that drought stress in the host did not increase pathogenicity of Sy. polyspora, indicating that it is a true endophyte of Scots pine.…”
Section: Culture-based Isolation and Hts Methods Complement Each Othermentioning
confidence: 98%
“…It can live asymptomatically as an endophyte in its host tree [6,7], and can transform from a latent to an opportunistic pathogen [8,9] or/and saprotroph [10]. In combination with stress-inducing factors, such as drought, hail, extreme temperatures, or mechanical wounding [11,12], S. sapinea may rapidly become pathogenic, leading to sudden disease outbreaks [13][14][15]. Ghelardini et al [16] considered that cryptic and latent pathogens, such as S. sapinea, are the most important drivers of emerging fungal diseases in forests.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations